1995
DOI: 10.1038/377649a0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of double-stranded DNA containing the major adduct of the anticancer drug cisplatin

Abstract: The success of cisplatin in cancer chemotherapy derives from its ability to crosslink DNA and alter the structure. Most cisplatin-DNA adducts are intrastrand d(GpG) and d(ApG) crosslinks, which unwind and bend the duplex to facilitate the binding of proteins that contain one or more high-mobility group (HMG) domains. When HMG-domain proteins such as HMG1, IXR (intrastrand-crosslink recognition) protein from yeast, or human upstream-binding factor (hUBF) bind cisplatin intrastrand crosslinks, they can be divert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
583
1
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(625 citation statements)
references
References 25 publications
31
583
1
7
Order By: Relevance
“…We assembled Pol II-nucleic acid scaffold complexes by incubating pure core Pol II with two molar equivalents of nucleic acid scaffold in transcription buffer (20 mM HEPES (pH 7.6), 60 mM (NH 4 ) 2 SO 4 , 8 mM MgSO 4 , 10 mM ZnCl 2 , 10% (v/v) glycerol, 10 mM DTT) at 20 1C for 30 min as described 8 . DNA strands containing the 1,2-d(GpG) and 1,2-(IpG) cisplatin intrastrand cross-links were synthesized as described 11 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assembled Pol II-nucleic acid scaffold complexes by incubating pure core Pol II with two molar equivalents of nucleic acid scaffold in transcription buffer (20 mM HEPES (pH 7.6), 60 mM (NH 4 ) 2 SO 4 , 8 mM MgSO 4 , 10 mM ZnCl 2 , 10% (v/v) glycerol, 10 mM DTT) at 20 1C for 30 min as described 8 . DNA strands containing the 1,2-d(GpG) and 1,2-(IpG) cisplatin intrastrand cross-links were synthesized as described 11 .…”
Section: Methodsmentioning
confidence: 99%
“…The change in the downstream DNA position results from the presence of the cisplatin lesion rather than from the scaffold design or the nucleic acid sequences, which were highly similar to those used previously 8 . Structures of free DNA containing a cisplatin lesion 10,11 reveal that the lesion at the center of the duplex leads to DNA bending. In our structure, the lesion is located at the end of the duplex and induces a slight repositioning of the downstream DNA, without substantial changes in its internal structure.…”
Section: Structure Of a Cisplatin-damaged Pol II Elongation Complexmentioning
confidence: 99%
“…Additionally, the products of reaction 1, corresponding to electrontransfer, may also arise via charge-transfer at a crossing point without proceeding through a long-lived complex. Previous ion/ion reaction studies involving multiply charged ions have suggested that charge-transfer at crossing points without long-lived complex formation can contribute significantly, in at least some cases, to electron-transfer [13][14][15]. Reactions 2 and 3, on the other hand, are expected to proceed via a long-lived complex.…”
Section: Computational Chemistrymentioning
confidence: 99%
“…Ruthenium(II) complexes have been extensively examined as spectroscopic probes of local DNA structure [11,12]. The mechanism of action of the chemotherapeutic agent cisplatin involves binding to DNA to prevent replication [13][14][15]. Mass spectrometry has been used as a tool for the examination of ODN complexes with metal ions [16].…”
mentioning
confidence: 99%
“…Similar to bifunctional alkylating agents, CIS interferes with DNA function by forming cross-links within DNA and between DNA and DNA-associated proteins (e.g., DNA polymerases, DNA topoisomerases, and histones) (3,4). Cellular studies have shown that the most frequent bivalent DNA adducts produced by CIS cross-link adjacent purines within one DNA strand, with a preference for guanines (5,6). Intramolecular links involving guanine (N7) are also formed, as are less frequent intermolecular links, representing an obstacle for DNA replication and transcription; the intramolecular links are relevant to drug cytotoxicity (7).…”
Section: Introductionmentioning
confidence: 99%